English National Identity and Football Fan Culture : Who Are Ya?. - Gibbons, Tom (Ashgate Publishing Ltd, 2014)
Examining football fans' expressions of Englishness in public houses and online spaces, the author discusses the effects of globalisation, European integration and UK devolution on English society, revealing that the use of the St George's Cross does not signal the emergence of a specifically 'English' national consciousness, but in fact masks a more complex, multi-layered process of national identity construction. A detailed and grounded study of identity, nationalism and globalisation amongst football fans, English National Identity and Football Fan Culture will appeal to scholars and studen.